Analisis Tingkat Kepahaman Sistem Rujukan Berjenjang Terhadap Kepuasan Pasien BPJS di Rumah Sakit Umum Daerah Ir. Soekarno Kabupaten Sukoharjo - Primanda Budi Utami; Muhlizardy Muhlizardy (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Background; In Indonesia, the referral system is organized in a tiered form, which functions as part of the system and relates to each other. Satisfaction is a very important indicator in measuring health services in hospitals. The problem that often occurs in a tiered referral system that affects patient satisfaction is that patients do not understand the tiered referral system. The objectives of the research; Analyzing the level of understanding of the tiered referral system on BPJS patient satisfaction at RSUD Ir. Soekarno Sukoharjo Regency. Methods; This type of research is quantitative with descriptive research design. Result; The level of understanding of the tiered referral system with BPJS patient satisfaction obtained that 4 respondents had a low level of understanding felt less and quite satisfied. A total of 41 respondents had a moderate level of understanding although there were still respondents who felt less satisfied and satisfied, but most respondents who had a moderate level of understanding felt quite satisfied. A total of 10 respondents had a high level of understanding and were satisfied. Summary; There is a significant relationship between the level of understanding of the tiered referral system and BPJS patient satisfaction at Rumah Sakit Umum Daerah Ir. Soekarno Sukoharjo Regency.